1990
DOI: 10.1111/j.1528-1157.1990.tb05365.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Training on Aerobic Capacity, Seizure Occurrence, and Serum Level of Antiepileptic Drugs in Adults with Epilepsy

Abstract: Twenty-one adult in-patients (11 women, 10 men, aged 18-39 years) with uncontrolled epilepsy participated in a 4-week intensive physical training program, exercising for at least 45 min three times a day, 6 days a week, at an intensity of minimum 60% of maximum oxygen uptake (maximum VO2). The program induced a considerable increase in maximum VO2 (mean 19%). Beneficial psychological and social effects were also recorded. The average seizure frequency during the 4-week exercise period was compared with 2 preex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
1
11

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 14 publications
4
99
1
11
Order By: Relevance
“…This finding of fear as an exercise deterrent is in accordance with current research [1,4,7,8,10,30,31], however, the qualitative approach taken allowed for the diverse ways in which fear manifested itself to be revealed. Such manifestation included the fear that seizures could prevent Maya from achieving her end goal and would cause teammates to keep away from Andrew at the gym, as well as create the feelings of a loss of independence for Rose and Gwen.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding of fear as an exercise deterrent is in accordance with current research [1,4,7,8,10,30,31], however, the qualitative approach taken allowed for the diverse ways in which fear manifested itself to be revealed. Such manifestation included the fear that seizures could prevent Maya from achieving her end goal and would cause teammates to keep away from Andrew at the gym, as well as create the feelings of a loss of independence for Rose and Gwen.…”
Section: Discussionsupporting
confidence: 88%
“…For most people with epilepsy, physical activity has been shown to have positive effects on seizure control and personal well-being [1]. Recently, the International League Against Epilepsy (ILAE)'s task force on sports and exercise promoted these benefits and provided clinical advice on how to exercise safely in regards to level of seizure control [2].…”
Section: Introductionmentioning
confidence: 99%
“…These differences may be associated with the social isolation commonly observed in people with epilepsy 28,29 . Similarly, Nakken et al 9 observed that a 4-week exercise program improved the mental state and sociability of people with epilepsy. Furthermore, a regular exercise program improved performance and psychosocial quality of life of women with refractory epilepsy 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, regular exercise contributes to mood-related benefits 4 and minimizes the impact of stressful life events 5 ; similar results have been found in people with epilepsy 6,7 . The favorable effects of regular exercise on physical fitness and general health are unquestionable and numerous studies have reported positive effects of regular physical activity in people with epilepsy 6,7,8,9,10,11,12 . Regular physical activity has been proposed as a positive coping strategy in the management of patients with epilepsy that are diagnosed with mood disorders 13,14 .…”
mentioning
confidence: 99%
“…The literature demonstrates that epileptiform discharges on EEG decrease during exercise 1-3 . Physical activity reduces seizure frequency, as well as lead to improved cardiovascular and psychological health in persons with epilepsy 4 . It has been also observed that fewer seizures occur during both mental and physical activity compared with periods of rest 5 .…”
mentioning
confidence: 99%